The Dynamic model of speech interruptions - Кириченко, Тетяна Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article explores the dynamic model of speech interruptions. The analysis revealed the main components of the dynamic model of speech interruptions in dialogic interaction. The article describes the main phases (pre-interruption, interruption itself and post-interruption phase), which are a part of interruption process in dialogic discourse. The article also analyses basic features of each phase of the interruption. The results of the research are bolstered with examples of dialogic discourse taken from the works of contemporary British and American authors of the XX – XXI centuries. At the end of the article conclusions are presented and prospects for the further study of interruptions in speech interaction are formulated.